Calculation of Tax Effective Yields: A Correction - Colin, J. W.; Dyl, Edward A. (Journal of Financial and Quantitative Analysis, 1971)
A recent article in this journal [1] described a model for the computation of taxadjusted true yields to maturity on discount bonds and explained the use of a computer routine implementing this model. Unfortunately, the translation of the computer program into equation form contained a number of notational errors. In addition, there was an equals sign missing from the third equation [1, page 267]. As a result, the reader, in attempting to implement the model as it was formulated in the original article, will probably fail.